Effects of personal air pollution exposure on asthma symptoms, lung function and airway inflammation. Issue 7 (10th April 2018) - Chambers, L.; Finch, J.; Edwards, K.; Jeanjean, A.; Leigh, R.; Gonem, S.
Summary: Background: There is evidence that air pollution increases the risk of asthma hospitalizations and healthcare utilization, but the effects on day‐to‐day asthma control are not fully understood. Objective: We undertook a prospective single‐centre panel study to test the hypothesis that personal air pollution exposure is associated with asthma symptoms, lung function and airway inflammation. Methods: Thirty‐two patients with a clinical diagnosis of asthma were provided with a personal air pollution monitor (Cairclip NO2 /O3 ) which was kept on or around their person throughout the 12‐week follow‐up period. Ambient levels of NO2 and particulate matter were modelled based upon satellite imaging data. Directly measured ozone, NO2 and particulate matter levels were obtained from a monitoring station in central Leicester. Participants made daily electronic records of asthma symptoms, peak expiratory flow and exhaled nitric oxide. Spirometry and asthma symptom questionnaires were completed at fortnightly study visits. Data were analysed using linear mixed effects models and cross‐correlation. Results: Cairclip exposure data were of good quality with clear evidence of diurnal variability and a missing data rate of approximately 20%. We were unable to detect consistent relationships between personal air pollution exposure and clinical outcomes in the group as a whole. In an exploratory subgroup analysis, total oxidant exposure was associated with increased daytime symptoms in women but not men. Conclusions and clinical relevance: We did not find compelling evidence that air pollution exposure impacts on day‐to‐day clinical control in an unselected asthma population, but further studies are required in larger populations with higher exposure levels. Women may be more susceptible than men to the effects of air pollution, an observation which requires confirmation in future studies.